Dendritic cell are able to differentially recognize Sporothrix schenckii antigens and promote Th1/Th17 response in vitro - Verdan, F. F. [UNESP]; Faleiros, J. C. [UNESP]; Ferreira, L. S. [UNESP]; Monnazzi, L. G. S. [UNESP]; Maia, D. C. G. [UNESP]; Tansine, A. [UNESP]; Placeres, M. C. P. [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Santos-Junior, R. R. [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
Sporotrichosis is a disease caused by the dimorphic fungus Sporothrix schenckii. The main clinical manifestations occur in the skin, however the number of systemic and visceral cases has increased, especially in immunocompromised patients. Dendritic cells (DCs) are highly capable to recognize the fungus associated data and translate it into differential T cells responses both in vivo and in vitro. Although, the mechanisms involved in the interaction between DCs and S. schenckii are not fully elucidated. The present study investigated the phenotypic and functional changes in bone marrow dendritic cells (BMDCs) stimulated in vitro with the yeast form of S. schenckii or exoantigen (ExoAg) and its ability to trigger a cellular immune response in vitro. Our results demonstrated that the live yeast of S. schenckii and its exoantigen, at a higher dose, were able to activate BMDCs and made them capable of triggering T cell responses in vitro. Whereas the yeast group promoted more pronounced IFN-gamma production rather than IL-17, the Exo100 group generated similar production of both cytokines. The exoantigen stimulus suggests a capability to deviate the immune response from an effector Th1 to an inflammatory Th17 response. Interestingly, only the Exo100 group promoted the production of IL-6 and a significant increase of TGF-beta, in addition to IL-23 production. Interestingly, only Exo100 group was capable to promote the production of IL-6 and a significant increase on TGF-beta, in addition with IL-23 detection. Our results demonstrated the plasticity of DCs in translating the data associated with the fungus S. schenckii and ExoAg into differential T cell responses in vitro. The possibility of using ex vivo-generated DCs as vaccinal and therapeutic tools for sporotrichosis is a challenge for the future. (c) 2012 Elsevier GmbH. All rights reserved.
Keywords: DCs; Immunomodulation; T cell; S. schenckii; Exoantigen